Partisipasi Masyarakat Nelayan di Sumatera Utara dalam Pembuatan Kebijakan Ditinjau dari Perspektif Hak Atas Pembangunan - Hakki Fajriando (Badan Strategi Kebijakan Hukum, 2015)
Over the past few years, fisherman communities become the focus of various government pro-poor policies. However, reality shows those programmes have failed to increase the degree of life of fishermen in Indonesia and reduce poverty among fisherman. One of the issues was the lack of compatibility of those programs with fisherman's needs, due to the lack of their participation in policy-making process. The right to development outlined that the preparation and implementation of development programs should prioritize public participation and the active role of the community, from the planning, all the way to the implementation, monitoring and evaluation of those programs. This article seeks to analyze the involvement of fishing communities in North Sumatra in the planning and budgeting process of those government programs. As a qualitative research, data collection is done through Focus Group Discussion and in-depth interviews that were supported by literatery study. The results showed that the participation of fishing communities in North Sumatra in policy-making is relatively minimal. Likewise, planning and budgeting some fisheries program aimed at fishermen does not directly accomodate their participation. Recommendations given are that the involvement of groups of poor fishermen can be instituted, as a formal mechanism for fisherman to channel their aspirations directly to enable it to be accommodated by the government.